Volumetry and Analysis of Anatomical Variants of the Anterior Portion of the Petrous Apex Outlined by the Kawase Triangle Using Computed Tomography - Adams Pérez, Juliano; Rassier Isolan, Gustavo; Pires de Aguiar, Paulo Henrique; Antunes, Apio Martins (Journal of Neurological Surgery Part B: Skull Base, 2014)
Background Anterior petrosectomy has become an increasingly used approach for petroclival lesions. This study measures the volume and the anatomical variants of the anterior portion of the petrous apex outlined by the Kawase triangle using computed tomography (CT).Methods This was a transversal retrospective study. We assessed the anterior petrous apex portion outlined by the Kawase triangle in consecutive patients > 18 years of age from CT scans of temporal bone stored in an archive system. The volumetry was performed on a workstation.Results A total of 154 petrosal apex were analyzed in 77 patients (36 men). The average volume of the region outlined by the Kawase triangle was 1.89 ± 0.52 cm3. The volume average in men was 2.01 ± 0.58 cm3, and the average in women was 1.79 ± 0.41 cm3. Intra- and interobserver agreement were both excellent, and there was little variance. Nineteen petrous apex demonstrated anatomical variations. In 18 cases it was pneumatized, and in one case a vascular or nerve-like structure was identified, a report we did not find in the literature.Conclusion The volumetry of the petrous apex anterior portion outlined by the Kawase triangle can be made by CT with excellent intra- and interobserver agreement and reproducibility. There are anatomical variants in this region that are relevant to surgery.
Keywords: petrous apex; volumetry; Kawase triangle; surgical approach